Case Report: Pure Red Cell Aplasia Caused by Refractory Parvovirus B19 Infection After Pancreas Transplantation Alone - Lindahl, Jørn Petter; Barlinn, Regine; Abrahamsen, Ingerid Weum; Spetalen, Signe; Midtvedt, Karsten; Jenssen, Trond (Frontiers in Medicine, 2022)
A multidisciplinary team of doctors is in charge or is involved in the follow-up of patients who undergo solid organ transplantation (SOT). Immunosuppressive drugs are required after SOT, some potential unwanted side effects can be difficult to detect, and physicians must be aware of potential pitfalls. We report a case of a recipient with brittle type 1 diabetes who experienced severe and refractory anemia after pancreas transplantation alone (PTA). Despite a broad diagnostic approach for anemia, the diagnosis was delayed. The patient had normocytic normochromic anemia with severe reticulocytopenia and marked reduction or absence of erythroid precursors in the bone marrow, compatible with pure red cell aplasia (PRCA). Analyses of serological parvovirus B19 anti-IgM and anti-IgG antibodies, including PCR, were initially inconclusive/negative. The diagnosis of parvovirus B19 infection was confirmed after bone marrow biopsy with immunohistochemical staining for parvovirus B19. A retrospective analysis revealed an early post-transplant primary parvovirus B19 infection. The patient was successfully treated with intravenous immunoglobulin (IVIg) therapy. There is a risk of diagnostic delay for the less common types of anemia following SOT. Parvovirus B19 infection-associated PRCA is curable in SOT recipients and should be actively considered in patients with persistent anemia and low reticulocytes.